2014
DOI: 10.1037/neu0000038
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal growth and neuropsychological performance in preterm-birth preschoolers.

Abstract: Among postnatal anthropometric indices, preschool stature, rather than head circumference, remains a consistent correlate of preschool outcome in preterm children, highlighting the contribution of general physical development to neuropsychological performance. Further investigation of the underlying mechanisms likely involves exploration of complex relationships between postnatal nutrition, growth hormone levels, body and brain development, and neuropsychological functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 80 publications
(133 reference statements)
0
8
2
Order By: Relevance
“…These negative findings seem inconsistent with the notion that early gains in lean body mass (and, therefore, linear growth) are closely related to organ (including brain) growth and differentiation (Ramel et al, 2012). Although in our earlier, cross-sectional, study (Raz et al, 2014), we found some support for Ramel et al’s expectation that functional outcome will be linked to length measurements, the current results did not lend support to their thesis. The absence of significant relationships between early postnatal linear growth and neuropsychological functioning at preschool age may be partly due to reduced accuracy of length measurements in newborns, likely associated with the difficulty in keeping children fully stretched-out and still (WHO Multicentre Growth Reference Study Group, 2006).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These negative findings seem inconsistent with the notion that early gains in lean body mass (and, therefore, linear growth) are closely related to organ (including brain) growth and differentiation (Ramel et al, 2012). Although in our earlier, cross-sectional, study (Raz et al, 2014), we found some support for Ramel et al’s expectation that functional outcome will be linked to length measurements, the current results did not lend support to their thesis. The absence of significant relationships between early postnatal linear growth and neuropsychological functioning at preschool age may be partly due to reduced accuracy of length measurements in newborns, likely associated with the difficulty in keeping children fully stretched-out and still (WHO Multicentre Growth Reference Study Group, 2006).…”
Section: Discussioncontrasting
confidence: 99%
“…The study of postnatal anthropometric data obtained from children born preterm, conducted in the past two decades, involved examination of head size (Charkaluk et al, 2011; Cheong et al, 2008; Cooke, 2005; Kuban et al, 2009; Kurdahi Badr, Bookheimer, Purdy, & Deeb, 2009; Raz, Newman, DeBastos, Peters, and Barron, 2014; Rijken et al, 2007), body-length or stature (e.g., Heinonen et al, 2008, Ramel et al, 2012; Raz et al, 2014), and body-weight (e.g., Heinonen et al, 2008; Kan et al, 2008). In this at-risk population, anthropometric indices reflecting physical growth during single (e.g., Raz et al, 2014) or multiple (e.g., Cooke, 2006) developmental stages, spanning from hospital discharge (e.g., Ramel et al, 2012) to adolescence (e.g., Cooke, 2006), have been shown to be associated with neuropsychological outcome. Follow-up periods ranged from infancy (e.g., Ramel et al, 2012) to preschool or school-age (Cooke, 2006; Cooke & Foulder-Hughes, 2003; Kan et al, 2008; Peterson, Taylor, Minich, Klein, & Hack, 2006; Raz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear whether, and to what extent, sample characteristics contributed to the differences in the results. At any case, in a recent study of extreme preterm birth (Raz et al, 2010), where sample selection criteria for gestational age were more similar to those of Kan et al (2008), we reported an incidental finding of significant relationships between the intrauterine growth z score and cognitive skills. In our study of VPT children, with and without bronchopulmonary dysplasia (Newman, Debastos, Batton, & Raz, 2011), we documented a similar trend.…”
mentioning
confidence: 52%
“…In the Neonatal Intensive Care Unit (NICU) setting, optimizing cardiorespiratory function takes precedence in therapeutic targeting to improve mortality. It is well recognized that long-term neurodevelopmental outcomes beyond mere survival are critically dependent on nutrition and optimal growth [26]. Protein accretion in turn is dependent on cellular acid-base status, electrolyte homeostasis, and the conservation of micro- and macroelements.…”
Section: Reviewmentioning
confidence: 99%